Risk assessment of food supply : a computable general equilibrium approach - Tanaka, Tetsuji (Cambridge Scholars Pub., 2012)
In recent years, food prices have been volatile worldwide. High and fluctuating food prices have led to riots in many low income countries, and have increased the world poverty population. Both developed and developing nations are rushing to buy farmland, even outside their own countries, for their future food security, which indicates that it has been more difficult to secure food supplies. This book addresses the issue of agricultural trade liberalisation by Japan, factors behind the world ...